Lista de la flora vascular de la cuenca superior del Río Savegre, San Gerardo de Dota, Costa Rica - Kappelle, Maarten; van Omme, Liz; Juárez, Marta E. (Instituto de Ecología, A.C., 2000)
This paper presents a checklist of the vascular plant species found in the upper watershed of the Savegre River (2 000-3 491 m above sea level), San Gerardo de Dota, Los Santos Forest Reserve, Cordillera de Talamanca, Costa Rica. Alpine páramo vegetation, subalpine dwarf forests, upper and lower montane cloud forests, as well as man-induced montane vegetation types such as pasturelands, fernbrakes, shrublands, secondary forests and tree plantations, were sampled. A total of 626 species in 121 families have been identified. 123 species of pteridophytes, 1 of conifers, 385 of dicots and 117 of monocots were recorded. The most diverse families are Asteraceae (57 species), Orchidaceae (51), Rubiaceae (26), Elaphoglossaceae (23), Polypodiaceae (23) and Poaceae (19), while the most species-rich genera are Elaphoglossum (23 species), Polypodium (14), Epidendrum (12), Peperomia (12), Asplenium (9), Blechnum (9) and Ocotea (9). Herbaceous plants (including ferns and allies) comprise 56.2% (352 species), whereas trees, shrubs and climbers make up 22.4% (140 species), 15.3% (96) and 6.1% (38) of the flora, respectively. Of the total number of species, 19.5% (122 spp.) are epiphytes. Four species (recently described Asteraceae and Lauraceae, as well as an Asteraceae and a Cyperaceae as yet undescribed) are new to science. The upper and lower montane mature forests and the upper montane secondary forests are the most species-rich plant communities, containing 264, 267 and 227 vascular plant species, respectively. The richness of the last is the consequence of the presence of numerous herbaceous species originally found in páramo vegetation and subalpine dwarf forest, which migrated downslope after forest conversion in the upper montane mature forest zone. The great diversity of lower montane mature forests is due to the presence of species mainly distributed at altitudes below 2 000 m above sea level reaching their uppermost limit precisely in this vegetation type.